1989
DOI: 10.1093/ajcp/92.6.760
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prostate-Specific Antigen and Prostate Pathology in Men Having Simple Prostatectomy

Abstract: Prostate-specific antigen (PSA) is a sensitive and specific serum marker for monitoring disease activity in men with prostatic carcinoma. Despite reports of elevation of levels of this analyte in men with benign prostatic hyperplasia, no information is available correlating the serum levels with the actual prostatic abnormalities in men having prostatectomy for presumed benign disease. In the present investigation, the authors compared preoperative serum PSA levels with prostate disease in 81 men with bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…Conversely, Alexander et al [27]evaluated radical prostatectomy specimens and found that high-grade PIN volume did not contribute to serum PSA concentration. Our findings are compatible with the reports of Brawer et al [25]and Bostwick et al [26]. We demonstrated that tPSA values in patients with PIN were higher than the patients with BPH and lower than the patients with CaP.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Conversely, Alexander et al [27]evaluated radical prostatectomy specimens and found that high-grade PIN volume did not contribute to serum PSA concentration. Our findings are compatible with the reports of Brawer et al [25]and Bostwick et al [26]. We demonstrated that tPSA values in patients with PIN were higher than the patients with BPH and lower than the patients with CaP.…”
Section: Discussionsupporting
confidence: 94%
“…Brawer et al [25]studied the correlation of preoperative serum PSA levels between BPH and PIN in patients who underwent simple prostatectomy. The mean serum PSA value was 5.6 ng/ml for patients with isolated PIN, 2.1 ng/ml for those with benign disease, and 35.1 ng/ml for patients with carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is the disruption of this barrier by disease which allows an in¯ux of PSA into the systemic circulation. 1 Embryologically, while the prostate utricle is derived from the MuÈ llerian tubes (equivalent of the vagina), the majority of the gland is derived from the uro-genital sinus. This is an androgendependent process.…”
Section: Anatomy and Biology Of The Prostatementioning
confidence: 99%
“…Although several reports have suggested that BPH and prostatic inflammation contribute to an increase in total serum PSA concentration [11, 12, 13, 14, 15, 16], it remains to be proved whether the presence of pathologically abnormal areas of the prostate affected by BPH allow leakage from the prostatic acini and ductule lumen into the systemic circulation and thus increase the serum F-PSA and total PSA (T-PSA) concentrations.…”
Section: Introductionmentioning
confidence: 99%